Parenteral Iron Sucrose Therapy for Moderate and Severe Iron-Deficiency Anemia in Pregnancy - Esin, Sertac; Yırcı, Bülent; Zengin, Tuğba; Yalvaç, Serdar; Kandemir, Ömer (Gynecology Obstetrics & Reproductive Medicine, 2016)
Objective: Parenteral iron therapy for iron deficiency anemia is gaining popularity due to its fast and impressing action. However, effectiveness and safety of iron sucrose in pregnant patient population is less clear. In this study, we aimed to review our intravenous iron sucrose use in pregnant patients. Study Design: The medical records of all anemic pregnant patients hospitalized for parenteral iron sucrose therapy were reviewed retrospectively. Results: The results of 117 pregnant women were available. Thirty-one (26.5%) and 86 (73.5%) of the patients were in the 2nd and 3rd trimester of the pregnancy, respectively. Four (%3.4) of the patients had severe and 113 (%96.6) of the patients had moderate anemia. The median gestational age for iron sucrose administration was 31.1 weeks (26.8-34.3). The mean hemoglobin, hematocrit and ferritin levels before and after delivery were 10.8±1.3 gr/l; 9.9±1.3 gr/l, 33.5±4.0; 30.8±4.0 and 89.6±0.7 μg/L; 98.1±0.9 μg/L, respectively. All but 2 (1.8%) patients had elevated hemoglobin levels after iron sucrose therapy. When hemoglobin and hematocrit levels were compared between before iron sucrose therapy and before delivery, there was a 2.8 g/l and 7.8 % increase in the mean hemoglobin and hematocrit levels, respectively and the difference was statistically significant (p= 0.001 and p=0.001, respectively). Five patients (4.3%) reported mild hypersensitivity reaction to intravenous iron in the form of mild itching at the infusion site. No severe or life-threatening hypersensitivity reaction was reported. Conclusion: In this study, we found out that intravenous iron sucrose therapy for iron deficiency anemia is feasible, effective and has a good safety profile.